Minimum wages and the welfare of workers in Honduras - T. H. Gindling; Katherine Terrell (Institute for the Study of Labor (IZA), 2007)
Taking advantage of a complex minimum wage structure in Honduras, this paper examines how changes in minimum wages over the 1990-2004 period affect unemployment as well as the employment and average wages of workers in different sectors of the economy: medium and large-scale firms v. small firms in the private sector (where minimum wage legislation applies) and civil servants and self-employed workers (where it does not apply). The evidence suggests that minimum wages are effectively enforced only in medium and large-scale firms, where a 1% increase in the minimum wage leads to an increase of 0.29% in the average wage and a reduction in employment of -0.46%. We find that increases in the private sector minimum wage are emulated in public sector wages, but there are no disemployment effects there. There is some evidence that a higher minimum wage may increase unemployment. There are no discernable effects of minimum wages on the wages of workers in small-firms or the self-employed. The positive impact of higher minimum wages on average wages is greatest for the primary educated in large private firms; but this group also suffers a very large disemployment effect. We conclude that, even in the sector where minimum wages are enforced and even under our upper bound estimate of the effect on the wages of workers, the welfare - the total earnings - of low-paid workers in the large-firm covered sector falls with higher minimum wages.
Keywords: 330; Mindestlohn; Wirkungsanalyse; Einkommen; Beschäftigungseffekt; Arbeitslosigkeit; Honduras